Abiotic Stress and Biofertilizer on The Pereskia bleo (Kunth) DC. Against Growth, Proline, and Antioxidants - Intan Christin Dullah; Sulandjari Sulandjari; Supriyono Supriyono (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
Pereskia bleo is a spiny bush from the genus Pereskia and family Cactaceae. Its leaves are shiny green, flowering, and fruitful. Some researchers to indicate that P.bleo leaves contain high antioxidants, anti-cancer, and are traditionally used for diabetic, hemorrhoids, hypertension, and gastric pain. The aim of this study was to determine the effect of salinity stress and water volume as well as the role of biofertilizer on the growth of Pereskia bleo and antioxidant content. Using Nested design (completely randomized factorial) with NaCl treatment; 0 ppm, 5 ppm, 10 ppm, and biofertilizer; 5 ppm, 10 ppm, each nested in a water volume of 500 ml, 300 ml and 150 ml per polybag. Each treatment was repeated three times, resulting in a total sample of 54 plants. Meanwhile, the findings indicate that abiotic pressure suppresses growth and proline, but not on antioxidants. There is an interaction between salinity and biofertilizer against antioxidants. Abiotic Stress can increase the antioxidant content.